2017
DOI: 10.1007/s10897-017-0158-8
|View full text |Cite
|
Sign up to set email alerts
|

Projecting the Supply and Demand for Certified Genetic Counselors: a Workforce Study

Abstract: As of May 2017, there were 4242 Certified Genetic Counselors (CGC) (American Board of Genetic Counseling, Inc. 2017) and 41 graduate-level genetic counseling training programs (Accreditation Council for Genetic Counseling 2017) in North America, and the demand for CGCs continues to increase. In the Fall of 2015 the Genetic Counselor Workforce Working Group, comprised of representatives from the American Board of Genetic Counseling (ABGC), the Accreditation Council for Genetic Counseling (ACGC), the Association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
236
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(241 citation statements)
references
References 0 publications
4
236
0
1
Order By: Relevance
“…These numbers can be compared to Accreditation Council for Genetic Counseling (ACGC) statistics, inferring that around 700–800 new graduates entered the workforce during this same three year period (Accreditation Council for Genetic Counseling, ). This would seem to confirm the fast growth of the occupation as indicated in other reports (Hoskovec et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These numbers can be compared to Accreditation Council for Genetic Counseling (ACGC) statistics, inferring that around 700–800 new graduates entered the workforce during this same three year period (Accreditation Council for Genetic Counseling, ). This would seem to confirm the fast growth of the occupation as indicated in other reports (Hoskovec et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, the number of job openings has consistently been larger than the number of genetic counseling graduates (Hoskovec et al, ). In our study, we found a strong job market with 1594 individual jobs posted on the NSGC Job Connection and 373 openings posted through ABGC from 2014 to 2016.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a critical part of training of the next generation of genetic counselors, and it is a required element of GC graduate programs accredited by the Accreditation Council for Genetic Counseling (ACGC, ). Given the high demand for genetic counselors (Hoskovec et al, ), there are increasing numbers of GC training programs, and existing programs are working on increasing the sizes of their classes. However, two of the top six reasons program directors state for not being able to expand their training program are related to a lack of proper supervision (Pan, Yashar, Pothast, & Wicklund, ).…”
Section: Introductionmentioning
confidence: 99%
“…A commissioned GC workforce analysis estimated that there will be 3,755 GCs in direct patient care positions in 2025. Projected demands for GCs in direct patient positions ranged from 3,473 (281 surplus) to 4,631 (876 deficit) (Hoskovec et al, ). In the absence of a sufficient number of GCs to meet the growing demand for services, current practitioners need to evaluate how they can increase their efficiency to ensure adequate access.…”
Section: Discussionmentioning
confidence: 99%